Evaluasi Program Sistem Pertanian Terintegrasi (Simantri) - Dewi, Ni Putu Andepi; Sujana, I Nyoman; Meitriana, Made Ary (Jurnal Pendidikan Ekonomi Undiksha, 2020)
This study aimed at investigating the extent of effectiveness of the Simantri in Mangani Village in 2018 in terms of context, input, process and product. The instruments that were used in this study were quesyionnaires and documentation. The members of Simantri in Mengani Village consisted oif 39 people were used as the subject of the study and the object was the Simantri program. This study used descriptive analysis by using standard score (z-crore) transformed into T-score then verified into the prototype from Glickman. The result of the data analysis revealed that from each dimension, context obtained a positive result (+), input obtained a negative result (-), the process obtained a positive result (+) and the product also obtained a positive result (+), then the CIPP position (+ - + +) in quadrant II. So, it can be concluded that the implementation of the Simantri program in Mengani Village was included in quite effective category.